Clinical outcomes in COVID‐19 patients treated with tocilizumab: An individual patient data systematic review. Issue 11 (9th June 2020) - Antwi‐Amoabeng, Daniel; Kanji, Zahara; Ford, Brent; Beutler, Bryce D.; Riddle, Mark S.; Siddiqui, Faisal
Abstract: Background: Current evidence suggests an important role of the interleukin‐6 (IL‐6) pathway in severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐related cytokine release storm in severely ill coronavirus disease 2019 (COVID‐19) patients. Inhibition of the IL‐6 pathway with tocilizumab has been employed successfully in some of these patients but the data is mostly consistent of case reports and series. Methods: We performed a systematic search of PubMed, Embase, and Medline from 22nd April 2020 and again on 27th April 2020 using the following search terms alone or in combination: "COVID‐19, " "coronavirus, " "SARS‐CoV‐2, " "COVID, " "anti‐interleukin‐6 receptor antibodies, " "anti‐IL‐6, " "tocilizumab, " "sarilumab, " "siltuximab." We included studies that reported individual patient data. We extracted and analyzed individual level data on baseline characteristics, laboratory findings, and clinical outcomes. The primary endpoint was in‐hospital mortality. Secondary endpoints included in‐hospital complications, recovery rates, effect of patient characteristics on the primary outcome and changes in levels of inflammatory markers. Results: Three hundred fifty‐two records were identified through a systematic search, of which 10 studies met the inclusion criteria. A single study currently under review was also added. Eleven observational studies encompassing 29 patients were included in the present review. There were more males (24 [82.8%]), and hypertension was the most common comorbidity (16 [48.3%]). Over an average of 5.4 hospital days, the primary endpoint occurred in 6 (20.7%) patients. Among surviving patients, about 10% had worsened disease and 17% recovered. The most common complication was acute respiratory distress syndrome (8 [27.6%]). The IL‐6 level was significantly higher after the initiation of tocilizumab with median (interquartile range) of 376.6 (148‐900.6) pg/mL compared to the baseline of 71.1 (31.9‐122.8) pg/mL ( P  = .002). Mean (standard deviation) levels of C‐reactive protein (CRP) were significantly decreased following treatment 24.6 (26.9) mg/L compared to baseline 140.4 (77) mg/L ( P  < .0001). Baseline demographics were not significantly different among survivors and nonsurvivors by Fisher's exact test. Conclusion: In COVID‐19 patients treated with tocilizumab, IL‐6 levels are significantly elevated, which are supportive of cytokine storm. Following initiation of tocilizumab, there is elevation in the IL‐6 levels and CRP levels dramatically decrease, suggesting an improvement in this hyperinflammatory state. Ongoing randomized control trials will allow for further evaluation of this promising therapy. Importance: Recent data indicate that severe COVID‐19 causes a cytokine release storm and is associated with worse clinical outcomes and IL‐6 plays an important role. It is suggestive that anti‐IL‐6 results in the improvement of this hyperinflammatory state. However, to our knowledge, there is no individual patient data systematic review performed to summarize baseline characteristics and clinical outcomes of COVID‐19 patients who received tocilizumab. Highlights: Interleukin‐6 (IL‐6) may play an important role in the pathogenesis of COVID‐19. Data show that tocilizumab, an IL‐6 receptor antagonist, reduces COVID‐19 complications. Our systematic review suggests that tocilizumab may improve survival in COVID‐19.